Analysis of the Influence of Additional Plastic Waste (HDPE) as Mixed Asphalt AC-WC on Marshall Parameters - Karonsih Widyapsari Boru Pinem, Hendriquita; Pristyawati, Tantin; Aski Safarizki, Hendramawat (Universitas Ibn Khaldun Bogor, 2022)
Flexible pavement structures that use asphalt as a binder are currently the mainstay of the Indonesian people because of their large load-bearing capacity and economical construction costs. One type of flexible pavement used is asphalt concrete with the top surface layer or Asphalt Concrete Wearing Course (AC-WC). The use of asphalt from the petroleum refining process is one of the problems because its availability is decreasing. However, the condition of the road pavement which has a limited life requires periodic repairs to maintain the condition of the road. In addition, there are also problems regarding the processing of plastic waste which is still not optimal. Based on data published by the National Waste Management Information System in 2020 as much as 18.3% of the total waste generated. This figure increased by 2.3% from the previous year. Sukoharjo Regency also experienced an increase in sales of plastic waste by 1.16% from 14.04% (in 2019) and now to 15.20% (in 2020). Plastic is one type of polymer in the thermoplastic polymer group which is processed by organic chemical compounds. One type of plastic that is often used is High Density Polyethylene (HDPE) which has strong, light and flexible properties that can soften at a temperature of 130-137